2022
DOI: 10.9745/ghsp-d-22-00162
|View full text |Cite
|
Sign up to set email alerts
|

Networks of Care: An Approach to Improving Maternal and Newborn Health

Abstract: The Networks of Care approach has the potential to harmonize existing strategies and optimize health systems functions for maternal and newborn health, thereby strengthening the quality of care and ultimately improving outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
1
7
0
2
Order By: Relevance
“…12 Building on this definition, a landscape review led by WHO, identified key structural and relational elements of networks working to improve maternal and newborn healthcare (fig 1). 13 Networks of care share characteristics with other approaches that target the organisation of a health system to improve performance. For example, networks may be nested within district health systems but also include links to tertiary care facilities or may cross administrative boundaries.…”
Section: Defining Network Of Carementioning
confidence: 99%
See 3 more Smart Citations
“…12 Building on this definition, a landscape review led by WHO, identified key structural and relational elements of networks working to improve maternal and newborn healthcare (fig 1). 13 Networks of care share characteristics with other approaches that target the organisation of a health system to improve performance. For example, networks may be nested within district health systems but also include links to tertiary care facilities or may cross administrative boundaries.…”
Section: Defining Network Of Carementioning
confidence: 99%
“…They were defined as “a group of public and/or private health service delivery sites deliberately interconnected through an administrative and clinical management model which promotes a structure and culture that prioritizes client-centered, effective, efficient operation and collaborative learning, enabling providers across all levels of care, not excluding the community, to work in teams and share responsibility for health outcomes.”12 Building on this definition, a landscape review led by WHO, identified key structural and relational elements of networks working to improve maternal and newborn healthcare (fig 1). 13…”
Section: Defining Network Of Carementioning
confidence: 99%
See 2 more Smart Citations
“…In a commentary summarizing a landscape review of Networks of Care conducted by the World Health Organization, Kalaris et al 1 argue that Networks of Care can improve quality and continuity of care and strengthen health systems functions by improving relationships between different providers—and that all these improvements will accelerate progress toward the Sustainable Development Goals.…”
mentioning
confidence: 99%